Dying to kill : the allure of suicide terror - Bloom, Mia, 1968- (Columbia University Press, 2005)
"Mia Bloom examines the use, strategies, successes, and failures of suicide bombing in Asia, the Middle East, and Europe and assesses the effectiveness of government responses. She argues that in many instances the efforts of Israel in the Middle East, Russia in Chechnya, and the United States in Iraq have failed to deter terrorism and suicide bombings. Bloom also considers how terrorist groups learn from one another, how they respond to counterterror tactics, the financing of terrorism, and the role of suicide attacks against the backdrop of larger ethnic and political conflicts."--Jacket